WITHDRAWING TREATMENT AND KILLING: THE WAYS TO DISTINGUISH - Rassudina, Kateryna S. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2020)
One of the key problems facing bioethics concerns those cases where, due to the limited human and technical resources of medicine, patients are in fact doomed to die. The reason for withdrawing treatment may be the futility of using the available means, as well as the burden of certain procedures. In the contemporary world, euthanasia is offered as an alternative to withdrawing treatment, that is, direct causing the death of a patient, killing. They distinguish these two types of practice by analyzing the duties of the physician, the intentions of all subjects, the differences between action and inaction. The obligation to save the patient at all costs should be rejected because of the non-humanity of this principle. That is why, however, the doctor faces a dilemma: to leave the patient to natural processes (it can cause, however, his or her additional suffering), or to kill him or her directly. The intention in both cases is to solve a problem in which the treatment of the patient becomes futile, and the withdrawing sooner or later leads to death. Euthanasia in its passive form may procedurally coincide with the withdrawing treatment. Withdrawing treatment is the decision, and therefore, it is more an action than inaction. It seems that the choice between euthanasia and withdrawing treatment is purely technical. The author of the article suggests comparing the mechanisms of decision making in the application of euthanasia and withdrawing treatment, looking at the purpose of these decisions and the means of its reaching. In the case of euthanasia, the purpose of action or inaction is to relieve suffering (a certain good), and the means is to cause death. In the case of withdrawing treatment, instead, the goal is also the good of the patient, but death is not a means but a side effect. Therefore, the author recognizes that withdrawing treatment is a more moral practice than euthanasia, which is a direct killing and is justified by the low value of one’s life.